DRUG PATTERN STUDY ON ANGIOTENSIN II RECEPTOR BLOCKER IN OUTPATIENTS AT MOHAMMAD HOESIN HOSPITAL PALEMBANG - Samantha Ferlin Boentara; Theodorus Theodorus; Nita Parisa (Fakultas Kedokteran Universitas Sriwijaya, 2022)
Hypertension is a global health problem due to its increasing prevalence. Hypertension is a condition where there is a persistent increase in blood pressure exceeding 140/90 mmHg. Among the many choices of antihypertensive drug classes, ARB is one of the first-line drug classes for the treatment of hypertension. Inappropriate ARB administration can reduce the effectiveness of treatment and harm the patient. This study aims to determine the pattern of ARB use in hypertensive patients. This drug pattern study has been done on October – November 2021 at the Outpatient Department of Dr. Mohammad Hoesin Central Public Hospital Palembang. The sample was using the medical record data of all hypertensive patients’ period of July – December 2020 who met the inclusion criteria, with a total of 171 data. The data was processed by using the SPSS v25 and presented in the form of a table with a descriptive explanation referring to the research variables. This study found that the prevalence of ARB use was 59.0% with the highest was in male (30.4%) and age group 41-60 years (29.2%). The most widely used ARB is candesartan (94.0%) at a dose of 16 mg (52.6%), frequency once a day (97.9%) and duration more than one month (93.7%). The drug prescribed to the patient mostly didn’t have interaction with ARB (33.0%). The prevalence of ARB administration is high in hypertensive patients (59.0%) with the most commonly used ARB is candesartan (94.0%).